PENGARUH PENGGUNAAN LEMBAR KEGIATAN PESERTA DIDIK BERBASIS INKUIRI TERBIMBING TERHADAP KEMAMPUAN KONEKSI MATEMATIS PESERTA DIDIK - Asnirul Jannah; Dinny Mardiana (UJMES (Uninus Journal of Mathematics Education and Science), 2020)
This research was motivated by the low of students’ mathematical connection ability. Guided inquiry-based student worksheets was used as an alternative to improve students' ability. The purpose of this research was determine the effect of using guided inquiry-based student worksheets on students' mathematical connection ability in mathematics learning. The research was conducted in one of the state junior high school in the city of Bandung. The population in this study were all VII grade students, with the sample were VII 4 class students as the control class and VII 9 class as the experimental class. The instruments used were a matter of students’ mathematical connection ability test and observation sheet of educator activities. Based on the analysis of the Cohen's d test, it was concluded that the use of guided inquiry-based student worksheets affected students' mathematical connection ability.